2006
DOI: 10.1093/intqhc/mzl031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health care professionals’ and surveyors’ opinions on problems and obstacles in implementing quality management system in Thailand: a national survey

Abstract: Health care professionals have been facing many problems with multidisciplinary process-related issues of the accreditation standard, whereas surveyors might have had some difficulties in conveying the core QI concepts to them. The findings might be explained by the effects of health care reform on the underlying accreditation principles. One of the strategies to respond to the situation was presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 12 publications
5
31
0
2
Order By: Relevance
“…These findings are similar to those of other studies in the United States (Messner, 1998), Switzerland (Hudelson et al, 2008), Thailand (Pongpirul et al, 2006), Iran (Rad, 2005), Indonesia (Amar & Zain, 2002), and Taiwan (Lin & Jang, 2008). These researchers found that some or all of these factors (lack of rewards for hospital staff, inadequate authority delegation, and lack of staff) were major obstacles.…”
Section: Major Qms Obstacles In High-and Low-performing Hospitalssupporting
confidence: 88%
See 2 more Smart Citations
“…These findings are similar to those of other studies in the United States (Messner, 1998), Switzerland (Hudelson et al, 2008), Thailand (Pongpirul et al, 2006), Iran (Rad, 2005), Indonesia (Amar & Zain, 2002), and Taiwan (Lin & Jang, 2008). These researchers found that some or all of these factors (lack of rewards for hospital staff, inadequate authority delegation, and lack of staff) were major obstacles.…”
Section: Major Qms Obstacles In High-and Low-performing Hospitalssupporting
confidence: 88%
“…The questionnaire was based on the Quality Management Systems Obstacles Scale (QMSOS) which was built based on a comprehensive literature review of QMS and several survey instruments. The questionnaire is consisted of a list of the most common 23 concepts derived from various studies (Desai, 2010;Dixon-Woods et al, 2012;Hudelson et al, 2008;Lin & Jang, 2008;Pongpirul et al, 2006;Rad, 2005). This questionnaire is divided into two sections-A and B.…”
Section: Instruments Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in several countries (A'aqoulah et al 2016;Abdullah, Razak, Hanafi, & Jaafar, 2013;Lin & Jang, 2008;Pongpirul, Sriratanaban, Asavaroengchai, Thammatach, & Laoitthi, 2006) have reported on the existence of obstacles that hinder implementation of a QMS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers concluded that an organisation's performance and successful QMS implementation are positively related. Finally, Pongpirul et al (2006) explored the obstacles that hinder implementation of QMSs in Thailand hospitals based on hospital accreditation standards. The results demonstrated that there were obstacles to QMS such as utilisation and integration of information and quality improvement (QI) requirements.…”
Section: Literature Reviewmentioning
confidence: 99%